2021
DOI: 10.11604/pamj.2021.39.184.27977
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hypertensive medication access and affordability and their association with blood pressure control at a teaching hospital in Ghana

Abstract: Introduction many hypertensive patients require two or more anti-hypertensive drugs, but in low- and middle-income countries there may be challenges with medication access or affordability. The objective of this study was to determine accessibility and affordability of anti-hypertensive medicines and their association with blood pressure (BP) control among hypertensive patients attending the Korle-Bu teaching hospital (KBTH) polyclinic. Methods a cross-sectional study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…In settings or facilities where CV medicines are available, affordability is often a challenge. In settings or facilities where medicines are affordable or supplied free, availability is often a challenge [ 8 10 ]. Seven out of 11 studies reported availability less than 80%.…”
Section: Resultsmentioning
confidence: 99%
“…In settings or facilities where CV medicines are available, affordability is often a challenge. In settings or facilities where medicines are affordable or supplied free, availability is often a challenge [ 8 10 ]. Seven out of 11 studies reported availability less than 80%.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were conducted in low-income countries, namely, Ethiopia [ 8 ] and Rwanda [ 9 ]. Eleven studies were conducted in lower-middle-income countries, which are Angola [ 10 ], Tanzania [ 11 ], Senegal [ 12 ], Cameron [ 13 ], Nigeria [ 14 , 15 ], Ghana [ 16 , 17 ], Nepal [ 18 , 19 ], and Vietnam [ 20 ]. Whereas ten studies were undertaken in upper-middle-income countries, comprising China [ 21 , 22 , 23 , 24 , 25 , 26 ] and one study each for Brazil [ 27 ], Botswana [ 28 ], Iraq [ 29 ], and Peru [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The effect of patients’ access to hypertension care on hypertension outcomes was explored in 38% (15/39) of the included studies within seven SSA countries [34, 35, 37, 38, 47, 48, 5052, 54, 58, 63, 64, 66, 67]. The general trend was that the lower cost of care was significantly associated with better hypertension outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen cross-sectional studies were conducted in Ethiopia (n=3) [50][51][52], Nigeria (n=2) [53,54], Botswana (n=1) [55], Democratic Republic of Congo (n=1) [56], Swaziland now called Eswatini (n=2) [57,58], Namibia (1) [59], South Africa (n=3) [60][61][62], Ghana (n=4) [63][64][65][66] , Kenya (n=2) [67,68]. We additionally identified one quality improvement report from Botswana [69].…”
Section: Country and Design Of Included Studiesmentioning
confidence: 99%